A 5-Year Review of Acanthamoeba Keratitis Related to Wearing Contact Lenses in Korea. Issue 4 (July 2020) - Jo, Yeon Ji; Jang, Soo Kyung; Lee, Jieun; Lee, Jong Soo
Abstract : Purpose: To investigate the presentation, clinical characteristics, and outcomes of Acanthamoeba keratitis (AK) in Busan, South Korea, over a 5-year period. Methods: This retrospective study involved a review of the medical records of 16 patients (19 eyes in total) who were diagnosed with AK, related to wearing contact lenses, at the tertiary hospital, Pusan National University Hospital at Busan City, from December 2013 to December 2018. Results: Nineteen eyes of 16 patients with a diagnosis of AK were identified. The average age of the patients was 21.1±12.6 years; there were 2 men and 14 women. The mean period from the onset of the first symptoms to diagnosis was 7.0±6.5 days. The average initial visual acuity was 0.78±0.37 (tested on a logarithm of the minimum angle of resolution chart), and the final visual acuity after treatment was 0.07±0.07, indicating a significant improvement ( P =0.001). A variety of corneal lesions were identified. Early diagnosis of AK was associated with a significantly better final visual acuity. Conclusion: The average therapeutic period for AK, when a surface epithelial lesion of the cornea was identified, was 4 months compared with an average period of over 6 months for a deeper stromal lesion. Therefore, this study highlights the fundamental importance of early diagnosis, preventing deeper layers of the cornea from being affected, and appropriate management to ensure a favorable outcome.